Corporate governance efficiency and internet financial reporting quality. Issue 1 (4th February 2014) - Botti, Laurent; Boubaker, Sabri; Hamrouni, Amal; Solonandrasana, Bernardin
Abstract : Purpose: – This paper aims to shed some light on the role of boards of directors in improving internet financial reporting (IFR) quality. Design/methodology/approach: – The empirical study uses a data envelopment analysis (DEA) approach on a sample of 32 French firms belonging to the CAC40 index as of December 2007. Findings: – The empirical results show that 28 percent of the sample firms are located on the efficiency frontier for all IFR components. These firms' boards of directors and their committees seem to act as effective monitors of top executives, which improves the quality of the firm's disclosure policy through, inter alia, an increase in the level of IFR. Under efficient board control, firms develop user-friendly and readily accessible web sites disclosing the information required by various stakeholders. Additional empirical results show that 46.9 percent of the sample firms lie outside the efficiency frontier for all IFR measures, suggesting inefficiencies in the composition, structure, and/or functioning of their boards of directors. The inefficient monitoring and oversight of top executives by the board allowed for lower levels of IFR quality for nearly half of the CAC40 firms in 2007. Research limitations/implications: – The study uses only CAC40 companies, which are relatively large and financially healthier than the average French firms, exhibiting diffuse ownership structures, with heavy foreign shareholding, and investing more in communications. This may limit the generalizability of the results to other French listed firms. Originality/value: – The paper extends the literature on corporate governance and voluntary corporate disclosure by investigating the association between board characteristics and IFR quality. It examines the relative performance of the board directors in improving IFR policy.